MODIFIKASI DIGITAL COMPRESSION TESTER SEBAGAI ALAT DIAGNOSA KEBOCORAN KOMPRESI PADA ENGINE TRAKTOR JOHN DEERE 6068 - Erik Tri Mahyudi; Bagas Prabowo; Endra Saputra; Luki Indratmoko (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2026)
Engine compression leakage testing is a crucial step in preventive maintenance to detect performance issues. However, conventional compression testers often have limitations in terms of accuracy and inefficient data documentation capabilities. Therefore, this research aims to modify a digital compression tester set to be a more accurate and efficient diagnostic tool for detecting compression leakage on John deere 6068 tractor engines. Testing was conducted by comparing the measurement results of the modified tool with a conventional tool on tractor engines experiencing a performance decline. Based on the research results that have been conducted, it can be concluded that the modification of the analog compression tester to a digital version has been successfully realized. The developed tool is capable of providing more accurate compression pressure measurement results with an average deviation of 0,56 % compared to the analog type of 3.88%.